(untitled) (Journal of Hama University, 2024)
The aim of the research is to study the dentoalveolar variables in the sagittal plane Following non-extraction treatment of class II using clear aligners and intermaxillary elastics, by studying lateral cephalometric radiographs. The research sample consisted of (12) patients whose ages ranged between (18-25) years, suffering from dental Class II malocclusion. They were treated by applying intermaxillary elastics with clear aligners starting at the first aligner, from hooks cut from the aligner material at the upper canines to buttons bonded to the buccal surface of the lower first molars. Lateral cephalometric radiographs were taken for all sample members at two times: T0 before starting treatment, and T1 after reaching a Class I occlusal relationship. the use of clear aligners with intermaxillary elastics led to a significant decrease P<0.05 in overjet by an average of 1.47 mm. It was also observed that a palatal tipping occurred in the upper incisors by an average (U1axisSN=4.39, U1axisSPP=3.98 degrees), while the lower incisors showed a buccal tipping an average of 1.91 degrees. It was also found that the upper first molar moved distally by an average of (U6-PTV=0.89 mm). All of these changes were statistically significant, P<0.05.